Pengaruh Modal Sendiri Terhadap Omzet Penjualan Pada koperasi Mahasiswa “Almamater” Universitas Negeri Makassar - Abdul Hafid; Ilham Abu (Fakultas Ekonomi Universitas Indonesia Timur, 2020)
The Makassar State University “alma mater” student cooperative is a cooperative engaged in the cadre field which includes entrepreneurship and entrepreneurship cadres which are expected to be able to direct the mindset of members who are more productive. The size of the cooperative business depends on the cooperative's ability to raise funds, both from their own capital and from loans. Capital has a role in efforts to increase cooperative business, with the cooperative's own capital, it can be used to increase cooperative business with the aim of increasing turnover in cooperatives. Based on preliminary observations of own capital, the student cooperative